The influence of hand positions on biomechanical injury risk factors at the wrist joint during the round-off skills in female gymnastics - Farana, R.; Jandacka, D.; Uchytil, J.; Zahradnik, D.; Irwin, G. (Journal of Sports Sciences, 2017)
The aim of this study was to examine the biomechanical injury risk factors at the wrist, including joint kinetics, kinematics and stiffness in the first and second contact limb for parallel and T-shape round-off (RO) techniques. Seven international-level female gymnasts performed 10 trials of the RO to back handspring with parallel and T-shape hand positions. Synchronised kinematic (3D motion analysis system; 247 Hz) and kinetic (two force plates; 1235 Hz) data were collected for each trial. A two-way repeated measure analysis of variance (ANOVA) assessed differences in the kinematic and kinetic parameters between the techniques for each contact limb. The main findings highlighted that in both the RO techniques, the second contact limb wrist joint is exposed to higher mechanical loads than the first contact limb demonstrated by increased axial compression force and loading rate. In the parallel technique, the second contact limb wrist joint is exposed to higher axial compression load. Differences between wrist joint kinetics highlight that the T-shape technique may potentially lead to reducing these bio-physical loads and consequently protect the second contact limb wrist joint from overload and biological failure. Highlighting the biomechanical risk factors facilitates the process of technique selection making more objective and safe.